Artificial Intelligencein Criminal Investigation - Yusep Mulyana; Subarsyah Subarsyah (International Journal of Law, Crime and Justice, 2024)
Artificial Intelligence (AI)plays a vital role in criminal investigations, offering innovative solutions to challenges faced by law enforcement. With its fast and accurate data analysis capabilities, AI can identify behavioral patterns, detect anomalies, and predict potential crimes. Technologies such as facial recognition, social network analysis, and natural language processing help speed up the investigation process and improve prosecution effectiveness. However, the application of AI also raises ethical challenges, including privacy issues and potential bias in algorithms. Therefore, it is important to develop a framework that ensures the responsible use of AI in a legal context.